The terror of the seas? : Scottish maritime warfare 1513-1713 - Murdoch, Steve (History of warfare, 2010)
This important new book provides the first detailed and clear analysis of the Scots involvement in naval warfare during the early modern period. The lazy use by both contemporaries and some modern authors of the word piracy as a catch-all for all sorts of maritime activity obscures a complex picture of Scottish maritime warfare. Through the use of letters of marque and reprisal (rightly distinguished in this analysis) as well as dedicated Crown fleets, Scottish warfare against against a wide range of enemies are scrutinised.